2018
DOI: 10.18311/jbc/2018/22477
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence of predatory bugs, Eocanthecona furcellata (Wolff) and Andrallus spinidens (Fabr.) on Spodoptera frugiperd (Smith) (Hemiptera:Pentatomidae) in maize and their potential in management of fall army worm

Abstract: Two species of predacious bugs, Eocanthecona furcellata (Wolff) and Andrallus spinidens (Fabr.) (Hemiptera:Pentatomidae) were found effectively preying on Spodoptera frugiperda (Smith) in organically grown maize from 28 to 56 days at GKVK, Bangalore. Population of E. furcellata in one square metre was more than A. spinidens during the 38 th and 39 th standard meteorological weeks. Adults and nymphs of both the species preyed on different stages of S. frugiperda larvae. These two species being initial colonizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 2 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…and Telenomus remus, was recorded from Shivamogga and Davanagere districts of Karnataka (Sharanabasappa et al 2020a). Two predatory pentatomids, Eocanthecona furcellata and Andrallus spinidens, feeding on the larva of fall armyworm are reported by Shylesha and Sravika (2018). During the monsoon season (kharif) 2018, natural infestation of entomopathogenic fungi, Metarhizium (¼Nomuraea) rileyi was noticed on S. frugiperda with its infection ranging from 1.87% to 18.30% (Mallapur et al 2018) and 10% to 15 % (Sharanabasappa et al 2019a).…”
Section: Biological Controlmentioning
confidence: 99%
“…and Telenomus remus, was recorded from Shivamogga and Davanagere districts of Karnataka (Sharanabasappa et al 2020a). Two predatory pentatomids, Eocanthecona furcellata and Andrallus spinidens, feeding on the larva of fall armyworm are reported by Shylesha and Sravika (2018). During the monsoon season (kharif) 2018, natural infestation of entomopathogenic fungi, Metarhizium (¼Nomuraea) rileyi was noticed on S. frugiperda with its infection ranging from 1.87% to 18.30% (Mallapur et al 2018) and 10% to 15 % (Sharanabasappa et al 2019a).…”
Section: Biological Controlmentioning
confidence: 99%
“…2) (Rezvani and Shahosseini 1976). Shylesha and Sravika (2018) found active feeding of both adults and nymphs on the different larval stages of Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) during the 38th and 39th standard meteorological weeks of maize growth when S. frugiperda caused severe damage. Bhojendra et al (2019) found no significant difference in predation rate among five sampling locations with different altitudes of A. spinidens in northwestern Himalayas.…”
Section: Distribution and Host Rangementioning
confidence: 99%
“…Andrallus spinidens has been reported in different geographical areas of eastern Asia, Australia, North Africa, some parts of Europe and North America [as a predatory bug of caterpillars damaging several agricultural crops including Helicoverpa armigera Hübner (Lepidoptera: Noctuidae)], Spodoptera litura Fabricius (Lepidoptera: Noctuidae), Chilo suppressalis Walker (Lepidoptera: Crambidae) and Naranga aenescens Moore (Lepidoptera: Noctuidae), Mythimna separate Walker (Lepidoptera: Noctuidae), Thermesia rubricans Boiduval (Lepidoptera: Noctuidae), Mythimna unipuncta Walker (Lepidoptera: Noctuidae), Melanitis leda L. (Lepidoptera: Nymphalidae), Pelopida smathias Fabricius (Lepidoptera: Hesperiidae), Spilosoma oblique Walker in addition to a coleopteran, Zygogramma bicolorata Pallister (Coleoptera: Chrysomelidae) (Lepidoptera: Erabidae) (Distant 1902;Maxwell-Lefroy 1909;Cherian and Brahmachari 1941;Rajendra and Patel 1971;Singh and Gangrade 1975;Pawar 1976;Rao and Rao 1979;Singh and Singh 1989;Pandey et al 2002;Mohaghegh and Amir-Maafi 2007;Claver and Jaiswal 2013;Shylesha and Sravika 2018;Bhojendra et al 2019).…”
Section: Distribution and Host Rangementioning
confidence: 99%
“…This polyphagous predator is amenable for mass production using laboratory lepidopteran hosts throughout the year and is easy to maintain and release. The insects can be released in the field at second or third nymphal stage so that they target the pests and manage them effectively (Shylesha and Sravika, 2018) and can suitably be exploited for pest management in organic vegetable production. This prompted to conduct detailed KEY WORDS: Biology, Eocanthecona furcellata, feeding potential, predator, Spilosoma obliqua (Article chronicle: Received: 09-03-2020; Revised: 11-05-2020; Accepted: 25-05-2020) studies on the biology and feeding potential of E. furcellata on S. obliqua, a lesser known prey of it.…”
Section: Introductionmentioning
confidence: 99%